PORNOGRAPHY EXPOSURE AND SEXUAL BEHAVIOR AMONG COLLEGE STUDENTS AT UNIVERSITAS JEMBER - N. Dyandra Agnefa Argadini; Ni mal Baroya; Devi Arine Kusumawardani (The Indonesian Journal of Public Health, 2026)
Introduction: Continuous exposure to pornography can lead to addiction. Pornography addiction is one of the leading causes of risky sexual behavior. The 2017 IDHS reported that 7.6% of male and 1.5% of female adolescents in Indonesia had sexual intercourse before marriage. A study conducted among college students at Universitas Jember showed that 6.3% had kissed, 5.4% had groped sensitive areas, and 3.6% had sexual intercourse. These results indicate a permissive attitude towards sexual behavior. Aims: To investigate the relationship between exposure to pornography and sexual behavior among college students at Universitas Jember. Methods: We conducted a cross-sectional study involving 154 students at Universitas Jember, from March to June 2024. Data were collected using structured interviews with questionnaires and analyzed using the chi-square test and Spearman's rank correlation with α = 0.05 (5%). Results: The results revealed that all respondents had been exposed to pornography, and most were classified as having high-risk sexual behavior. Bivariate analysis revealed a positive relationship between exposure to pornography and risky sexual behavior (p-value: <0.001; rs = 0.388). Conclusion: Riskier sexual behavior increases with higher levels of pornography addiction. It is recommended that Universitas Jember organize comprehensive education on reproductive health for its students.